THE INFLUENCE OF REWARD AND PUNISHMENT TOWARD EMPLOYEE’S PERFORMANCE AT BANK INDONESIA BRANCH MANADO - Panekenan, Regitha M.; Tumbuan, Willem J.F.A; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: This study takes an object of research at Bank Indonesia. One of the companies involved in the world of banking company. Make employees to improve their performance optimal. The big companies also implement compensation systems reward and punishment that is sufficiently stringent. The purpose of this study is to know the influence of reward and punishment toward employee performance at Bank Indonesia Branch Manado. This research use a multiple regression analysis with total sample 40 respondents which are the employee at Bank Indonesia Branch Manado. The result shows that reward and punishment are significantly influence the employee performance simultaneously and partially. The employee feel honored by the reward that given by the company and it drive the employee’s motivation to work harder and make a better performance. The employee take the punishment in a positive way as a lesson and make the punishment as the driving force to motivate them more and create a better performance. The human resource department of Bank Indonesia Branch Manado DAOP 8 should keep their great performance by adding more reward in purpose to make the employee performance better and should keep make the employee think positive about their punishment. Keywords: reward, punishment, employee performance